Scaffolding Language Teacher Education: Criteria-Based Evaluation of Language Practice Activities - Mitić, Svetlana S. (Collection of Papers of the Faculty of Philosophy in Priština, 2024)
This paper addresses the development of a key teacher competence—activity evaluation, as well as adaptation and design—to cater for mixed-ability classes. In the context of English as a foreign language (EFL) teacher education, the question is how early, within what framework, and under what procedures students should be taught this competence. Practicum teaching at university has been found to lack in validity, learner-centeredness, and heterogeneity, be it at the level of an activity, a series of activities, a lesson, or a series of lessons. Action research was conducted to address this issue, basing a part of an introductory English Language Teaching (ELT) methods course on developing students’ awareness and putting into practice Ur’s seven principles of activity conceptualisation, with a particular focus on validity, volume, and heterogeneity. The students were asked to apply these principles in teaching mock-up lessons to their peers and to analyse to what extent the principles qualified their peers’ lessons and the practice of in-service teachers they observed in primary and secondary schools. The content analysis of the students’ reports shows the majority both comprehended and consistently applied most of the principles, while a small number demonstrated a proper and thorough understanding of all the criteria, consistently and correctly applying them in their observation reports and in designing and teaching their mock-up lessons. Very few students consistently adopted some of the concepts incorrectly or non-specifically. No comprehensive analysis is offered of how the students’ mock-up lessons were guided by the activity evaluation criteria explored. It remains to be seen if and to what extent students apply the principles in the final-year practicum, after criteria-based activity evaluation, adaptation, and design are integrated in their second ELT methods course, which focuses on developing skill teaching.
Keywords: language teacher education; student teacher; mock-up lesson; language practice activity; validity; volume; heterogeneity